2016
DOI: 10.1002/ps.4365
|View full text |Cite
|
Sign up to set email alerts
|

Systemic RNAi in the small hive beetleAethina tumidaMurray (Coleoptera: Nitidulidae), a serious pest of the European honey beeApis mellifera

Abstract: This is the first study to show evidence for systemic RNAi in A. tumida in response to injected dsRNA, but further research is required to develop methods to induce RNAi effects via ingestion. © 2016 Crown copyright. Pest Management Science © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 42 publications
4
39
0
1
Order By: Relevance
“…Not surprisingly, due to the lack of sequence similarity, dsSK also showed no effects. A similar observation in A. mellifera was reported by Powell et al ., who demonstrated that injections into honeybees of 50 ng of dsRNAs Laccase 2 and vacuolar ‐ATPase V‐type subunit A , designed to target Aethina humidity , similarly had no effect on bee survival and did not induce the suppression of either of the target genes. An alignment of A. mellifera and A. tumida Laccase 2 and V‐ATPase subunit A mRNAs indicated sequence identities of 74% and 68%, respectively.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Not surprisingly, due to the lack of sequence similarity, dsSK also showed no effects. A similar observation in A. mellifera was reported by Powell et al ., who demonstrated that injections into honeybees of 50 ng of dsRNAs Laccase 2 and vacuolar ‐ATPase V‐type subunit A , designed to target Aethina humidity , similarly had no effect on bee survival and did not induce the suppression of either of the target genes. An alignment of A. mellifera and A. tumida Laccase 2 and V‐ATPase subunit A mRNAs indicated sequence identities of 74% and 68%, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Stability studies of dsRNA provided proof that the dsRNA of the target genes was not degraded significantly during 48 h. Our results agree with those of Li et al ., which indicated that three dsRNAs targeting different sites within a gene encoding vacuolar ATP synthase subunit E in Nilaparvata lugens were found to be stable in 0.1 g mL –1 sucrose solution at 22 h. The Ap_ST1 dsRNAs (sugar transporter gene) from an aphid kept for a week at room temperature was not degraded, thus again demonstrating stability . However, 1 μg of V‐ATPase subunit dsRNA targeting A. tumida in 10 μL of 50% sucrose solution after 8 h is completely degraded . These contrasting results demonstrate the importance of evaluating the stability of specific dsRNAs under the appropriate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The level of sensitivity to RNAi by microinjection and oral exposure can be variable among insects within the same order. For example, in the Coleoptera order, D. virgifera virgifera , T. castaneum , Leptinotarsa decemlineata , Meligethes aeneus , Rhynchophorus ferrugineus , C. puncticollis , C. brunneus and A. planipennis are sensitive to both methods of dsRNA delivery, whereas Anthonomus grandis , Anthonomus eugenii and Aethina tumida are recalcitrant to RNAi by oral exposure . These studies demonstrate the importance of evaluating the RNAi sensitivity by microinjection as well as by feeding in the target insect species since it is not possible to predict the RNAi effectiveness based on the RNAi response found in other insects, even in closely related species.…”
Section: Discussionmentioning
confidence: 68%
“…V‐ATPase seems to be involved in growth and body formation in various orders of insects. Phenotypes of deformity induced by RNAi of V‐ATPases have been reported among several orders of insects including L. migratoria , A. tumida , and P. maidis (Li & Xia, ; Yao et al ., ; Powell et al ., ) (Fig. ).…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, functions of V-ATPases in insects have been studied only in species belonging to six orders (Orthoptera, Thysanoptera, Hemiptera, Coleoptera, Lepidoptera, Diptera) by RNA interference (RNAi), which can inhibit gene expression in a sequence specific manner by introduction of double-stranded RNA (dsRNA) (Miller et al, 2012;Miyata et al, 2014). Knockdown of V-ATPase causes lethal effect on various species suggesting this molecule is essential in vital physiological activities (Baum et al, 2007;Whyard et al, 2009;Gu et al, 2011;Upadhyay et al, 2011;Li & Xia, 2012;Khan et al, 2013;Yao et al, 2013;Badillo-Vargas et al, 2015;Jin et al, 2015;Rebijith et al, 2016;Powell et al, 2017). Therefore, V-ATPase has been proposed as a putative target molecule for the development of in planta dsRNA system to control insect pests (Baum et al, 2007;Kola et al, 2015).…”
Section: Introductionmentioning
confidence: 99%